Fermentasi Isothermal Biji Kakao (Theobroma cacao. L) dengan Sistem Aerasi Terkendali - Sri Hartuti; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Yudi Pranoto (agriTECH, 2018)
Cocoa bean fermentation is one of the important factors that must be done to produce high-quality chocolate. The success of the process is usually determined by changes in air temperature that occur during fermentation and the change in color of cocoa beans from purple to brown after going through a process of fermentation and drying. This study aims to determine the changes in the temperature of isothermal fermentation, as well as the quality of cocoa beans produced. Aeration rate and air temperature during fermentation are controlled to ensure optimal heat changes during the fermentation process. The parameters varied during the test were: the length of ripening of the cocoa fruit before fermentation, as well as the rate of aeration and the air temperature of the fermenter during fermentation. The results showed that during the fermentation process, there was an increase in the temperature of the cocoa beans from 25 °C to 63 °C. The results of the split test showed that the percentage of fermented cocoa beans was 67 - 87%, the percentage of partially fermented cocoa beans was 10 - 24% and unfermented cocoa beans 1 - 8%, and the average yield of dried cocoa beans was 38,5%. The fermented cocoa beans that have been carried out have met the quality standards of Indonesian cocoa beans (SNI 2323: 2008 / Amd 1: 2010).